Collagen-1 and elastin expression in cervical tissue: A comparison across cervical elongation, pelvic organ prolapse, and combined conditions - Widyasari, Anis; Hardianto, Gatut; Kusumastuti, Etty Hari; Kurniawati, Eighty Mardiyan (Universitas Airlangga, 2024)
HIGHLIGHTS Pathogenesis of cervical elongation is still limited, including the histological and molecular differences between a cervical elongation and a normal cervix. The expression of collagen-1 level in the cervical elongation group was stronger compared to the cervical elongation with POP and control group. ABSTRACT Objective: This study aimed to assess differences in the expression of collagen-1 and elastin in cervical tissues among patients with Cervical Elongation (CE), Pelvic Organ Prolapse (POP), a combination of CE with POP, and those without either condition. Materials and Methods: An analytical study with a cross-sectional design was conducted, using immunohistochemistry (IHC) to analyze cervical tissue samples preserved in paraffin blocks. Patient groups included those diagnosed with CE, POP, CE combined with POP, and a control group without CE or POP. All participants underwent surgery between January 2021 and April 2023. IHC was used to measure the expression levels of collagen-1 and elastin in each tissue sample. Observations were made under 400x magnification, focusing on five randomly selected visual-field areas in each sample to determine the area fraction. Two experienced pathologists conducted the analyses in a blinded manner to ensure objective evaluation. Results: Statistical analysis using the Kruskal-Wallis test revealed significant differences in the expression of collagen-1 across the four groups (CE, POP, CE with POP, and control). Patients with CE showed a higher expression of collagen-1 than those with CE and POP combined, as well as the control group. However, no significant differences in elastin expression were observed among the groups. Conclusion: Collagen-1 expression differs significantly across patients with CE, POP, and CE combined with POP, suggesting a distinct role in cervical tissue remodeling in these conditions. Conversely, elastin expression was consistent across all groups, indicating that it may not play a differentiating role in these pathologies. These findings highlight collagen-1’s potential involvement in the structural changes associated with CE and POP.